Would RMB appreciation lead to the liquidity trap in China? - Shi, Ziguo (KDI School, 2012)
With 30 years worth of high-speed development, currently the huge trade surplus generated the pressure of Chinese Yuan (RMB) appreciation. Many researchers worry about the economic outlook of China because Japan’s liquidity trap happened right after the appreciation of the Japanese Yen, and this concern has been a popular argument against RMB appreciation as well as the option of a floating exchange rate regime. However, even though Japan and Germany experienced the same currency appreciation, only Japan fell into the liquidity trap. This comparative study shows that currency appreciation was not the reason for Japan’s liquidity trap. Actually, the difference of interest rate between Japan and Germany took place right after the asset price bubbles burst in Japan, which undermined the effect of easy monetary policy in 1990s. Currently, China is facing the same conditions as what Japan and Germany experienced from the late 1980s to the early 90s. Ever since the appreciation of RMB in July 2005, China’s asset prices, like those of Japan, have rapidly increased. But China undertook monetary policies and administrative measures to prevent the rise of bubbles. Just like what was witnessed in Germany, China’s interest rate and inflation rate will correlate positively with the growth rate of monetary aggregate. In the future, if the Chinese authorities intervene in the foreign exchange market to delay the appreciation, then the market power would expect further appreciation. The continual expectation of appreciation would cause the inflow of abundant liquidity, which would increase interest and inflation rates in the long term. If no government intervention is involved in the foreign exchange rate, the capital inflow will lead the exchange rate to an equilibrium level as the market expects. Since the domestic liquidity is independent of the foreign exchange rate market, the inflation and interest rates will be immune to any fluctuations derived from the exchange rate.
Thesis(Master) --KDI School:Master of Public Policy,2012